2016
DOI: 10.1111/boj.12426
|View full text |Cite
|
Sign up to set email alerts
|

Morphoanatomy of the ovary and ovule in Bromeliaceae subfamily Tillandsioideae and its systematic relevance

Abstract: Tillandsioideae are composed of nine genera, most of these with unclear delimitation. The morphoanatomy of ovules and ovaries of 83 species from seven different genera was studied under light or scanning electron microscopy to contribute to the understanding of the relationships in the group. The nucellar epidermis and the parietal tissue showed a regular pattern for all Tillandsioideae. The presence of chalazal appendages, however, and their shape and size varied between the genera analysed. Most species had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…This result contrasts with previous phylogenetic studies based on morphological and molecular data, in which this species was nested in Tillandsia, in a sister position to Racinaea (Gomes-da-Silva & Souza-Chies, 2017). Unlike the other species of Vriesea, which have six to 12 columns of ovules in the locule, V. drepanocarpa only has four columns, similar to some species of Tillandsia and Racinaea (Kuhn et al, 2016). Therefore, the close position of V. drepanocarpa to Tillandsia and Racinea in the study of Gomesda-Silva & Souza-Chies (2017) might be explained by the fact that they included this morphological character in their phylogenetic analyses.…”
Section: Phylogenetic Relationships In Vrieseamentioning
confidence: 93%
“…This result contrasts with previous phylogenetic studies based on morphological and molecular data, in which this species was nested in Tillandsia, in a sister position to Racinaea (Gomes-da-Silva & Souza-Chies, 2017). Unlike the other species of Vriesea, which have six to 12 columns of ovules in the locule, V. drepanocarpa only has four columns, similar to some species of Tillandsia and Racinaea (Kuhn et al, 2016). Therefore, the close position of V. drepanocarpa to Tillandsia and Racinea in the study of Gomesda-Silva & Souza-Chies (2017) might be explained by the fact that they included this morphological character in their phylogenetic analyses.…”
Section: Phylogenetic Relationships In Vrieseamentioning
confidence: 93%
“…Embryological studies in Bromeliaceae are scarce, they involve, e.g., ovule and ovary positioning and morphology, androecium development and pollen viability, as well as embryonic development. These studies were reported by Conceição et al (2007), Kuhn et al (2016), Mendes et al (2010Mendes et al ( , 2012Mendes et al ( , 2014Mendes et al ( , 2016, Oliveira et al (2015) and Souza et al (2017).…”
Section: Introductionmentioning
confidence: 59%
“…Segecin and Scatena (2004a) also used anatomical characteristics of floral scapes of Tillandsia to differentiate similar species within the genus. Other authors also conducted studies involving rhizomes, roots, and nectaries, reinforcing that anatomical research is important regarding leaves and flowers and roots (Huhn, Nogueira, Fagundes, & Mariath, 2016;Mosti, Friedman, Pacini, Brighigna, & Panini, 2013;Segecin & Scatena, 2004b). These studies associate anatomical characteristics with environmental adaptations to the epiphyte habit of many Tillandsioideae species.…”
Section: Resultsmentioning
confidence: 98%